CORPORATE SOCIAL RESPONSIBILITY AS AN IMPORTANT FACTOR OF BUSINESS SUCCESS IN CROATIAN COMPANIES (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
Corporate social responsibility (CSR) is becoming an increasingly important subject of public discussion because application of this concept does not only affect company's business, but also the narrow and the wider community in which the company operates. The Republic of Croatia is an example of daily exposure of political and economic scandals, and the question arises to what extent the community and society are truly informed about the activities of many companies, and if there are written or unwritten laws and rules that seek to ensure adequate presence of morality in daily operations. The purpose of this study is to research the frequency of application of the concept of corporate social responsibility and code of ethics in companies (both public and private) in the Republic of Croatia and their effect. The paper tries to answer two research questions: a) how do Croatian companies perceive corporate social responsibility, and b) is there a link between corporate social performance of the company and signing the Code of business ethics. The empirical part of the paper is based on an anonymous survey of 95 respondents employed in different companies. The following parameters were investigated: respondents’ sociodemographic characteristics, familiarity with the concept of CSR, application in companies, year of introduction in the company, areas of application, and the effect that the application of corporate social responsibility has on the company. Furthermore, the level of presence of the code of ethics, and its availability and success in preventing non-ethical behaviour in companies were examined. The application of CSR and ethical business practice in Croatia has been rising in the past decade, but in order for the implementation to be fully successful, detailed changes of educational, economic and political systems are necessary.